Experimental Analysis and Electrical Modeling of PEM Fuel Cell's MEA - (:unkn) unknown (PRAISE WORTHY PRIZE SRL, 2010)
The proton exchange membrane fuel cell (PEMFC) which has low operating temperature, high power density and zero emission is the most suitable one for energy applications In this study. two different PEMFCs membrane electrode assemblies (MEA) are tested in terms of electrical characteristics in different temperatures and humidity Then these results are compared with improved PEMFCs electrical circuit model This model is developed in MATLAB/Simulink (R) Copyright (C) 2010 Praise Worthy Prize S.r.l. - All rights reserved.
Keywords: Experimental Analysis; Modeling; Fuel Cell; Membrane Electrode Assembly; SYSTEM